Pelaksanaan dan Pertanggung Jawaban APBD terhadap Pengelolaan Keuangan Daerah - Fajriatul Mukarramah Kasman (UIN Sunan Kalijaga Yogyakarta, 2017)
Management of Regional Finance is the whole activity that includes planning,implementation, administration, reporting, accountability, and supervision of localfinances. Regional financial management as regulated in this ministerial regulationincludes the power of regional financial management, the general principles and structureof the APBD, the drafting of APBD, the determination of APBD, the formulationand determination of APBD for regions that do not have DPRD, APBDimplementation, APBD changes, cash management, regions, regional financialaccounting, accountability of APBD implementation, development and supervision oflocal financial management, regional losses, and financial management. Regionalfinancial management starts with the planning / budgeting of regional expenditurebudget APBD. APBD is prepared in accordance with the needs of governance andlocal revenue capability. Preparation of APBD as directed to RKPD in order to realizethe service to the public for the achievement of the purpose of state. APBD has thefunctions of authorization, planning, supervision, allocation, distribution, andstabilization. APBD, APBD change, and accountability of APBD implementationevery year is stipulated by regional regulation. APBD compiled by the local governmenthas undergone a change from incramental to a performance-based budget in accordancewith the demands of reform. That APBD as a means of container to accommodatevarious public interest (public accountability) is realized through various activities andprograms, at which time certain benefits really felt by the general public. Localgovernments should work in a concrete and structured manner to generate APBDs thatreflect the real needs of the community in accordance with their respective potentials andmeet the demands of local budget-oriented interests and public accountability.